Needs Analysis of Pancasila Educational Comics as a Deep Learning Medium in Elementary Schools - Kurnia Putri, Devy Yuliastri; Triyatno, Triyatno; Zein Tarsidi, Deni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Learning Pancasila Education in elementary schools still tends to focus on memorization and does not fully support deep learning that is meaningful for students. This study aims to analyze the need for developing Pancasila educational comics as a deep learning-based learning media in elementary schools. The research method used is descriptive with a qualitative approach through interviews, observations, and documentation involving teachers and students. Data were analyzed through data reduction, data presentation, and drawing conclusions. The results revealed that teachers face limitations in using learning media that can present Pancasila material in a contextual, visual, and student-centered manner. In addition, students show a strong preference for story-based visual learning media that help them understand abstract Pancasila concepts more concretely. The available learning media are considered not yet optimal in supporting students’ cognitive engagement and conceptual understanding in depth. Therefore, the development of Pancasila educational comics is needed as an alternative learning medium that has the potential to support deep learning and enhance students’ cognitive understanding in elementary schools.